Quais são os fatores que estruturam as comunidades de girinos no pantanal em diferentes escalas e sub-regiões? - Simioni, Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
RESUMO Uma das principais abordagens em Ecologia envolve compreender a estrutura das metacomunidades e esclarecer quais processos ambientais e espaciais são responsáveis por promove-las. O Pantanal constitui um sistema interessante para avaliar a estrutura de metacomunidades de anuros por apresentar períodos de alagamentos que conectam as poças facilitando a dispersão dos anuros. Neste cenário, foram amostradas 75 comunidades de girinos em três sub-regiões o que possibilitou determinar, em escala local (cada sub-região) e ampla (todas as sub-regiões), a estrutura das metacomunidades, a influência relativa dos processos ambientais e espaciais na estrutura das metacomunidades e a congruência dos resultados nas três sub-regiões. De maneira geral encontramos pouca influência de processos espaciais e ambientais estruturando as metacomunidades. A inundação parece facilitar a dispersão dos anuros, explicando a fraca influência de processos espaciais. Já o hábito reprodutivo generalista da maioria das espécies, por aumentar o sucesso de colonização de novos habitats, explica a fraca influência das características ambientais na estrutura das metacomunidades. As estruturas detectadas corroboraram os resultados da influência relativa dos processos ambientais e espaciais. Em escala ampla e em duas das sub-regiões amostradas e foram detectadas quasi-estruturas (Nhecolândia e escala ampla) e estrutura aleatória (Porto Murtinho) que corroboram o fraco efeito estruturador do ambiente detectado na análise de processos. Miranda-Abobral foi a única sub-região que apresentou estrutura aninhada, corroborando a força do gradiente ambiental nessa metacomunidade, evidenciada pela análise de processos na qual foi a única sub-região com componente ambiental significativo. Nós detectamos que padrões e processos similares, relacionados a fraca ou nula influência ambiental, estruturaram as metacomunidades de girinos em cada sub-região do Pantanal. O pulso de inundação e a história de vida das espécies neste ambiente sazonalmente inundável são indicados como os fatores responsáveis pela estruturação dessas metacomunidades. ABSTRACT One of the main approaches in Ecology involves understanding the structure of metacommunities and clarifying the environmental and spatial processes responsible for it. The Pantanal floodplain is an interesting system for assessing anuran metacommunities structure because local periodic floods connect ponds and facilitate anuran dispersal. In this scenario, were sampled 75 tadpole metacommunities, in three sub-regions of the Pantanal, and evaluated in local (each subregion) and broad scale (all the subregions): the structure of the metacommunities, the relative influence of environmental and spatial processes and if the results are similar between the three subregions. In general, we find weak influence of spatial and environmental processes structuring the studied metacommunities. The flood seems to facilitate dispersal of the anurans, explaining the weak influence of spatial processes. By increasing the success in the colonization of new habitats, the generalist reproductive habits of most the species seem to explain the weak influence of the environmental features structuring the metacommunities. Structure types found here corroborated the results of the relative influence of the environmental and spatial process, reaffirming the complementarity of the methodologies. On broad scale and in two of the subregions sampled were detected quasi-structures (Nhecolândia and broad scale) and random structure (Porto Murtinho), supporting the weak structuring effect of the environment features in the process analysis. Miranda-Abobral was the only sub-region with a nested structure, confirming the strength of the environmental gradient in this metacommunity, as evidenced by the processes analysis in which was the only subregion with a significant environmental component. Miranda-Abobral was the only sub-region that did not present a quasi-structure but a nested structure instead and the only one with a significant environmental component, thus confirming the strength of the environmental gradient evidenced by the processes analysis. We detected similar patterns and processes structuring the tadpole metacommunities at each Pantanal sub-region. The flood pulse and the life history of the species in this seasonally flooded environment are indicated as the factors responsible for structuring these metacommunities.

One of the main approaches in Ecology involves understanding the structure of metacommunities and clarifying the environmental and spatial processes responsible for it. The Pantanal floodplain is an interesting system for assessing anuran metacommunities structure because local periodic floods connect ponds and facilitate anuran dispersal. In this scenario, were sampled 75 tadpole metacommunities, in three sub-regions of the Pantanal, and evaluated in local (each subregion) and broad scale (all the subregions): the structure of the metacommunities, the relative influence of environmental and spatial processes and if the results are similar between the three subregions. In general, we find weak influence of spatial and environmental processes structuring the studied metacommunities. The flood seems to facilitate dispersal of the anurans, explaining the weak influence of spatial processes. By increasing the success in the colonization of new habitats, the generalist reproductive habits of most the species seem to explain the weak influence of the environmental features structuring the metacommunities. Structure types found here corroborated the results of the relative influence of the environmental and spatial process, reaffirming the complementarity of the methodologies. On broad scale and in two of the subregions sampled were detected quasistructures (Nhecolândia and broad scale) and random structure (Porto Murtinho), supporting the weak structuring effect of the environment features in the process analysis. MirandaAbobral was the only sub-region with a nested structure, confirming the strength of the environmental gradient in this metacommunity, as evidenced by the processes analysis in which was the only subregion with a significant environmental component. Miranda-Abobral was the only sub-region that did not present a quasi-structure but a nested structure instead and the only one with a significant environmental component, thus confirming the strength of the environmental gradient evidenced by the processes analysis. We detected similar patterns and processes structuring the tadpole metacommunities at each Pantanal sub-region. The flood pulse and the life history of the species in this seasonally flooded environment are indicated as the factors responsible for structuring these metacommunities
What are the factors that structure the tadpoles communities in Pantanal at different scales and sub-regions?
Keywords: Estrutura de metacomunidades; Partição da variância; Escala ampla; História de vida; Metacommunity structure; Variation partitioning; Flood pulse; Broad scale; Life history